Allegories of the Anthropocene - DeLoughrey, Elizabeth M., 1967- (Duke University Press, 2019)
In 'Allegories of the Anthropocene' Elizabeth M. DeLoughrey traces how Indigenous and postcolonial peoples in the Caribbean and Pacific Islands grapple with the enormity of colonialism and anthropogenic climate change through art, poetry, and literature. In these works, authors and artists use allegory as a means to understand the multiscalar complexities of the Anthropocene and to critique the violence of capitalism, militarism, and the postcolonial state. DeLoughrey examines the work of a wide range of artists and writers-including poets Kamau Brathwaite and Kathy Jetnil-Kijiner, Dominican installation artist Tony Capellan, and authors Keri Hulme and Erna Brodber-whose work addresses Caribbean plantations, irradiated Pacific atolls, global flows of waste, and allegorical representations of the ocean and the island. In examining how island writers and artists address the experience of finding themselves at the forefront of the existential threat posed by climate change, DeLoughrey demonstrates how the Anthropocene and empire are mutually constitutive and establishes the vital importance of allegorical art and literature in understanding our global environmental crisis.